Bois de feu, maléfiques, bénéfiques, et la guerre des fumées (région de Maroua, Nord du Cameroun) - Christian Seignobos (Revue d'ethnoécologie)
During the independence years (1960) the section of a certain number of useful essences was prohibited and, with all the more reason, their wood could not be used to fuel hearths. A strict social control made sure of that. Some woods, however, presented a direct threat for the families if they were introduced accidentally or maliciously, in the hearths. Heads of households, sometimes with the help of seers or ritualists, had to fight these charms with antidotes from a range of plants whose fumes were supposed to get rid of the evil effect of the previous ones. This fumes war refers to cognitive frameworks which, in time, have hybridized to become sorts of meta-beliefs shared by many groups. The elders, as keepers of the agroforestry disciplines, were gradually removed, since the independence years, from their control over woods. Today, the relentless need for domestic fuel leads to a lack of differentiation between the essences, the neutrality of their woods and the standardization of the fumes.